Influence Of Organizational Culture And Work Ethics On Employee Performance Transportation Department In Merangin Regency - Herawati -; Khairun Roni; Wasis Mundi (Journal of Economics, Business, and Government Challenges, 2021)
Employee performance can be influenced by many factors, as well as in the Merangin District Transportation Office. This research examines the existing organizational culture and employee work ethics on 30 employee performance honorary staff. This research also wants to see which variable has the most influence on employee performance. This study uses a survey method in which the population and sample in this study are the same sizes or saturated sampling. The analytical tool in this study is SPSS with Multiple Linear Regression. The results found that organizational culture and work ethic enhance employee performance simultaneously and partially. Meanwhile, the contribution value of the two dependent variables on the independent variable was 53.4%. Further research can continue by adding other variables or can use different methods such as qualitative or mixed methods.